Epidemiology of pneumonia in hospitalized adults ≥18 years old in four districts of Ulaanbaatar, Mongolia, 2015–2019 - Kirsten Fagerli; Mukhchuluun Ulziibayar; Bujinlkham Suuri; Dashtseren Luvsantseren; Dorj Narangerel; Purevsuren Batsaikhan; Bilegtsaikhan Tsolmon; Bradford D. Gessner; Eileen M. Dunne; Anneke C. Grobler; Cattram D. Nguyen; Tuya Mungun; et al. (The Lancet Regional Health. Western Pacific, 2023)
Summary: Background: Community-acquired pneumonia is a leading cause of morbidity and mortality among children and adults worldwide. Adult pneumonia surveillance remains limited in many low- and middle-income settings, resulting in the disease burden being largely unknown. Methods: A retrospective cohort study was conducted by reviewing medical charts for respiratory admissions at four district hospitals in Ulaanbaatar during January 2015–February 2019. Characteristics of community-acquired pneumonia cases were summarized by disease severity and age. To explore factors associated with severe pneumonia, we ran univariable and age-adjusted logistic regression models. Incidence rates were calculated using population denominators. Results: In total, 4290 respiratory admissions met the case definition for clinical pneumonia, including 430 admissions of severe pneumonia. The highest proportion of severe pneumonia admissions occurred in adults >65 years (37.4%). After adjusting for age, there were increased odds of severe pneumonia in males (adjusted odds ratio [aOR]: 1.63; 95% confidence interval [CI]: 1.33-2.00) and those with ≥1 underlying medical condition (aOR: 1.46; 95% CI: 1.14-1.87). The incidence of hospitalized pneumonia in adults ≥18 years increased from 13.49 (95% CI: 12.58-14.44) in 2015 to 17.65 (95% CI: 16.63-18.71) in 2018 per 10,000 population. The incidence of severe pneumonia was highest in adults >65 years, ranging from 9.29 (95% CI: 6.17-13.43) in 2015 to 12.69 (95% CI: 9.22-17.04) in 2018 per 10,000 population. Interpretations: Vaccination and other strategies to reduce the risk of pneumonia, particularly among older adults and those with underlying medical conditions, should be prioritized. Funding: Pfizer clinical research collaboration agreement (contract number: WI236621).